On 3-Regular Bipancyclic Subgraphs of Hypercubes. (5th May 2015) - Borse, Y. M.; Shaikh, S. R.
Abstract : Then -dimensional hypercubeQ n is bipancyclic ; that is, it contains a cycle of every even length from 4 to2 n . In this paper, we prove thatQ n     ( n ≥ 3 ) contains a 3-regular, 3-connected, bipancyclic subgraph withl vertices for every evenl from 8 to2 n except 10.